The Role of Lyrics in Estonian Literature: Three Exemplary Cases - Anneli Niinre (Interlitteraria)
Song lyrics are usually positioned in the margins of literature and tend not to be in the first line when writers and their works are discussed. There have been debates about whether to consider lyrics as literature and/ or ‘real poetry’. The article examines three cases in Estonian literature where melodised poetic texts have played a significant role in Estonian culture and are considered to be core texts: “Mu isamaa on minu arm” (My Fatherland is My Love) by Lydia Koidula, songs from the feature film Viimne reliikvia (The Last Relic), lyrics written by Paul-Eerik Rummo, and “Laul Põhjamaast” (“Song of the Northern Land”), lyrics by Enn Vetemaa. These also represent three ways a text can function: “Mu isamaa on minu arm” was first written and published as a poem and later set to music; The Last Relic represents a case where texts were initially written as lyrics and later published in a collection of poems; “Song of the Northern Land”, by Enn Vetemaa, was meant to be and has remained a song and has not been included in poetry collections.